Critical mass effect and restructuring in the transition towards a market economy - Pier Luigi Sacco; Carlo Scarpa (Fondazione Eni Enrico Mattei (FEEM), 1998)
Restructuring firms in a transition economy produces a sort of network externality, in that the profitability of restructuring depends on the number of firms that already adopted this strategy. We investigate under what conditions a ''critical mass'' exists, i.e. a situation in which such extemality is positive, and restructuring spurs imitation, possibly leading to the eventual transformation of the whole economy. We find a critical mass effect when the main effect of restructuring is an increase in value added (i.e., aggregate demand) rather than an increase in the firm's ability to compete against rival home firms. The critical mass case becomes the typical one when competition spurs firms' efficiency.
Keywords: 330; Organisatorischer Wandel; Netzwerkökonomik; Systemtransformation; Theorie der Unternehmung; Theorie